2016
DOI: 10.2320/matertrans.m2016010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters of Backward Extrusion by Servo Press on Purification of A7075 Alloy under the Semisolid Condition

Abstract: The aggregation of tramp elements in repeated recycling processes is a growing problem and an effective technology for the separation of tramp elements from aluminium alloy scrap is necessary to produce new alloy products from old scrap. In this study, backward extrusion was conducted under the semisolid condition using a servo press (Komatsu-H1F110) to investigate the industrial-scale puri cation of A7075 wrought aluminium alloy. and, process parameters such as the semisolid temperature, backward extrusion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The increase of separation temperature will increase the amount of liquid phase and improve its flowability, which will lead to the increase of the filtrate amount. According to the study of ahmad and Cho, the solid fractions corresponding to each temperature in this work are 0.8 (609 °C ), 0.72 (617 °C ), 0.6 (625 °C ) [19,27]. The weight ratio of the residual accounting for the total weight is close to the theoretical solid fraction at the gravity coefficient of 1000 G. Thus, it is proved that the solid/liquid separation ratio with 1000 G is close to the theoretical value of solid/liquid fraction at different experimental temperatures.…”
Section: Effect Of Separation Temperaturementioning
confidence: 91%
See 2 more Smart Citations
“…The increase of separation temperature will increase the amount of liquid phase and improve its flowability, which will lead to the increase of the filtrate amount. According to the study of ahmad and Cho, the solid fractions corresponding to each temperature in this work are 0.8 (609 °C ), 0.72 (617 °C ), 0.6 (625 °C ) [19,27]. The weight ratio of the residual accounting for the total weight is close to the theoretical solid fraction at the gravity coefficient of 1000 G. Thus, it is proved that the solid/liquid separation ratio with 1000 G is close to the theoretical value of solid/liquid fraction at different experimental temperatures.…”
Section: Effect Of Separation Temperaturementioning
confidence: 91%
“…Cho etc. have performed comprehensive investigation on purification of aluminum alloys by backward extrusion process, but we think the refining effect may deteriorate quickly when applied to large scale experiments and the loss of aluminum is high for this method [5,19,20]. In the present work, for the aim of further enhancing the segregation tendency of liquid phase from grain boundaries and improving the separation efficiency, the super-gravity field generated by centrifugation was introduced in the rheorefining process of 7075 aluminum alloys.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is particularly important to address how to remove the low-melting-point Fe-rich phases from pure Al samples at lower temperatures [13,14]. Semi-solid processing for refining metal alloys was first introduced by Mehrabian [15] et al This method involves heating the metal to the temperature range of the solid/liquid coexistence and separating the solid and liquid phases through filtration treatment [16,17], electromagnetic force [10,[18][19][20][21], or gravitational sedimentation. Cho [16] et al investigated the industrial-scale purification of A7075 wrought Al alloy under semi-solid conditions using a servo press.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-solid processing for refining metal alloys was first introduced by Mehrabian [15] et al This method involves heating the metal to the temperature range of the solid/liquid coexistence and separating the solid and liquid phases through filtration treatment [16,17], electromagnetic force [10,[18][19][20][21], or gravitational sedimentation. Cho [16] et al investigated the industrial-scale purification of A7075 wrought Al alloy under semi-solid conditions using a servo press. It was confirmed that the purity of Al reached up to 95% at the semisolid temperature of 620 • C, with an extrusion ratio of 3 and an extrusion speed parameter of 25 mm/s.…”
Section: Introductionmentioning
confidence: 99%